A longitudinal study of maternal interaction strategies during joint book-reading in Taiwan. Issue 2 (6th March 2020) - CHANG, Chien-Ju; LUO, Ya-Hui
Abstract: This longitudinal study examines change in maternal interaction strategies in Taiwanese mothers across time, and the synchronic and diachronic relationships between maternal interaction strategies and children's language and early literacy skills. Forty-two mother–child dyads participated in this study. Their interactions during joint book-reading were tape-recorded, transcribed, and analyzed when the children were fourteen, twenty-six, and thirty-six months of age. The children received a battery of language and early literacy tests when they were thirty-six months old. Findings showed that Taiwanese mothers adjusted their use of interaction strategies as their children grew. Maternal use of description, performance, prediction inference, and print-related talk were positively correlated with their children's language and literacy skills. Significant negative correlations were found between use of task-behavioral regulation strategy and text reading in mothers and their children's language performance. This study suggests that age-appropriate interaction strategies are important for children's language and early literacy development.